Flexibilização de procedimentos e transporte de técnicas processuais nas ações de alimentos - Dias, José Eduardo Coelho (2023)
It seeks to assess the hypotheses and limits for the flexibility of procedures and the transport of procedural techniques from (projection or export) and to (reception or import) alimony actions with the use of bibliographical research. It highlights the relevance of substantive law for the formulation of procedures. Conceptualizes the alimony obligation. It discusses the types of alimony and characteristics of the alimony obligation. It seeks to distinguish fundamental concepts of procedural science, such as jurisdiction, action, process and procedure. Discusses special procedures. Conceptualizes the expression “procedural techniques”, addressing the conditions and limits for the flexibility of the procedure and the transport of procedural techniques. Discusses procedural flexibility and the transfer of procedural techniques in family processes. It analyzes the current alimony law, addressing its historical background. It analyzes the possibility of the alimony action flowing through the common rite It analyzes the situations of flexibility of procedure and transfer of procedural techniques in alimony actions. It concludes with the possibility of exporting and importing techniques foreseen in the special rite of maintenance actions for the common procedure, of the common procedure for the special rite of maintenance actions and in relation to other special procedures, suggesting some hypotheses.